Antibacterial activity of galam soap (Melaleuca cajuputi) against Salmonella typhi as a form of ethnoscience based learning - Muh. Azhari; Fathul Zannah (BIO-INOVED : Jurnal Biologi-Inovasi Pendidikan, 2022)
Central Kalimantan has abundant biodiversity, one of which is galam which is often found in swampy areas in Central Kalimantan. One example of the use of galam is processing it into soap products as an effort to manage plant-based waste typical of Central Kalimantan. This study aims to determine the antibacterial activity of galam soap (Melaleuca cajuputi) against Salmonella typhi bacteria, where the results of this study have the potential to be developed as a learning resource for the application of ethnoscience-based learning. This study used an experimental research method using the disc method and the research design was a Completely Randomized Design (CRD). The results showed that galam soap was effective in inhibiting the growth of Salmonella typhi bacteria. The results of these studies can be used as a learning resource in lecture activities as a form of implementation of ethnoscience-based learning using the results of recent research, because ethnoscience-based learning is expected to help create meaningful learning activities.Abstrak Kalimantan Tengah memiliki keanekaragaman hayati yang melimpah, salah satunya berupa galam yang seringkali ditemui pada wilayah rawa di Kalimantan Tengah. Salah satu contoh pemanfaatan galam diantaranya diolah manjadi produk sabun sebagai upaya untuk pengelolaan limbah berbasis tumbuhan khas yang ada di Kalimantan Tengah. Penelitian ini bertujuan untuk mengetahui aktivitas anti bakteri sabun galam (Melaleuca cajuputi) terhadap bakteri Salmonella typhi, dimana hasil penelitian tersebut sangat berpotensi untuk dikembangkan sebagai sumber belajar untuk penerapan pembelajaran berbasis etnosains. Penelitian ini menggunakan metode penelitian eksperimen dengan menggunakan metode cakram serta desain penelitiannnya berupa Rancangan Acak Lengkap (RAL). Hasil penelitian menunjukkan bahwa sabun galam terbukti efektif dalam menghambat pertumbuhan bakteri Salmonella typhi. Hasil penelitian tersebut dapat dimanfaatkan sebagai sumber belajar pada kegiatan perkuliahan sebagai bentuk implementasi dari pembelajaran berbasis etnosains menggunakan hasil-hasil penelitian terkini, karena pembelajaran berbasis etnosains diharapkan dapat membantu menciptakan kegiatan pembelajaran yang bermakna.